Analyzing the economic variables and their relationship to inflation in the US, China and Germany: Why empirical results demonstrate the inability to accurately assess economic policy through data - Rosa, Anthony Marino (Open Science Journal, 2020)
For the past 50 years, economists used the quantity theory of money to explain inflation. Monetarists, like Milton Friedman, view inflation as “everywhere a monetary phenomenon” and cite data comparing the quantity of money per unit of output (Real GDP) with CPI (inflation). Once scaled, the data appears strongly correlated. Critics state large action in the past decade by central banks did not lead to inflation. Recent research claims, “rapid money supply growth does not cause inflation...neither do rapid growth in government debt, declining interest rates, or rapid increases in a central bank’s balance sheet.” I test claims about the causes and predictability of inflation through a cross-country examination of different policies and their correlation with countries’ inflation rates. The study of inflation and its causes is important as the price mechanism is considered the mudsill of a functioning market, and countries aim to minimize large, unpredictable changes (hyperinflation, deflation). I examine empirical data from March 1959 - March 2020 in the United States through a multivariate linear regression model and then compare this with data from China 1996-2016 and Germany 1991-2020 as global references. I demonstrate the theoretical contradiction that, in the US, personal spending and high taxes correlate with inflation while government spending and monetary injections do not. I also demonstrate two key findings. First, interest rates appear to react to inflation rather than cause it. Second, there are no predictable causes of visible inflation in a global market. My results are inconclusive; yet the puzzling nature of their indications is evidence against broad monetary claims in general.